LATE CRETACEOUS SYNSEDIMENTARY TECTONIC IN EASTERN ATLAS SAHARAN (NORTH EAST OF ALGERIA) - Benmansour Sana (European Scientific Journal, ESJ, 2013)
This study focuses on the relations between sedimentary and tectonic, in the compression context of the terminal Cretaceous of Oriental Atlas Saharan (Tébessa). Paleogeography of the upper Senonian is influenced by the paleo-structure of the platform which determines the nature of the deposits and their geometry. From the tectonic point of view, the activity of the compressive phase eo-alpine increases during this period. This device shows a sedimentary and tectonic instability that accompanies the terminal Cretaceous sedimentation which is confirmed by the presence of synsedimentary structures (''Landslide'' slumps, normal faults). The correlation between the East Atlas Saharan and West during the Maastrichtian shows a differentiation in the geometry of deposits. It reflects the variation in subsidence and sedimentation rates between these two areas.